Regional planning of land resources uses and conservation in the Russian Federation - Evgeniia Y. Badamshina, Amir N. Kutliyarov, Ivan D. Stafiychuk, Damir N. Kutliyarov, Rail R. Khisamov, (Opción, 2020)
The purpose of the research is to study the potential of regional planning schemes use as an organizational basis for the rational use and conservation of all lands via the statistical data characterizing qualitative and quantitative indicators of the research object. As a result, according to the developed schemes which we analyzed, there is an unreasonable decrease in rural areas. In conclusion, in the future, a significant reduction in the area of agricultural land is expected as they will be used for housing, industrial needs, transport and recreation purposes